The Endothelial Mechanotransduction Protein Platelet Endothelial Cell Adhesion Molecule-1 Is Influenced by Aging and Exercise Training in Human Skeletal Muscle - Gliemann, Lasse; Rytter, Nicolai; Piil, Peter; Nilton, Jannik; Lind, Thomas; Nyberg, Michael; Cocks, Matthew; Hellsten, Ylva (Frontiers in Physiology, 2018)
Aim: The aim was to determine the role of aging and exercise training on endothelial mechanosensor proteins and the hyperemic response to shear stress by passive leg movement (PLM). Method: We examined the expression of mechanosensor proteins and vascular function in young (n=14, 25±3 years) and old (n=14, 72±5 years) healthy male subjects with eight weeks of aerobic exercise training. Before and after training, the hyperaemic response to PLM was determined and a thigh muscle biopsy was obtained before and after PLM to assess the acute effect of increased shear stress. Biopsies were analyzed for protein amount and phosphorylation of mechanosensor proteins; Platelet endothelial cell adhesion molecule-1 (PECAM-1), Vascular endothelial cadherin, Vascular endothelial growth factor receptor-2 and endothelial nitrc oxide synthase (eNOS). Results: Before training, the old group presented a lower hyperaemic response to PLM and a 35% lower (p<0.05) relative basal phosphorylation level of PECAM-1 whereas there was no difference for the other mechanosensor proteins. After training, the eNOS protein amount, the amount of PECAM-1 protein and the PLM-induced phosphorylation of PECAM-1 were higher in both groups. The hyperaemic response to PLM was higher after training in the young group only. Conclusion: Aged individuals have a lower hyperaemic response to passive leg movement and a lower relative basal phosphorylation of PECAM-1 than young. The higher PECAM-1 phosphorylation despite a similar hyperemic level in the aged observed after training, suggests that training improved shear stress responsiveness of this mechanotransduction protein.